Using Herringbone Technique to Improve Students’ Reading Comprehension at SMPN 21 Makassar - Maharani, Andi Aliah; Ariyani, Amra; Asriati, Asriati (Journal of Excellence in English Language Education, 2024)
The goal of this study is to ascertain how the Herringbone technique might be used at SMPN 21 Makassar to enhance students' reading comprehension. Since this study is pre-experimental, it is handled differently. The participants in this study were the eighth-grade students of SMPN 21 Makassar. Using the cluster random sampling approach, a single class—class 8E, which consisted of 27 students—was chosen at random to serve as the study's sample. A written test was administered both before and after therapy as part of the data-gathering procedure. Using IBM SPSS Version 27, the quantitative analysis of the writing test data was conducted to compare the test scores. The paired sample t-test was used to assess the results of the pre-and post-tests. According to the analysis, the average post-test score for the category of "not good" is 58.46, and the average post-test score for the category of "good" is 73.27. According to the study hypothesis, there is a noticeable difference in the reading comprehension of SMPN 21 Makassar students in the 8E class when they apply the Herringbone approach. Thus, it can be said that the 8E grade students at SMPN 21 Makassar benefit from using the Herringbone technique to increase their reading comprehension.